KERATINIZING SQUAMOUS CELL CARCINOMA NASAL - B. Hutagalung , Sanggam (Jurnal Kedokteran Methodist, 2022)
Background. Malignant tumors of the nasal cavity and paranasal sinuses are estimated to be 1% of all malignant human neoplasms and 3% of these are found in the head and neck. Typically found at the fifth and seventh ages and the ratio for men and women is 2: 1. Case report. A case was reported of a man who underwent nasal excision with a clinical diagnosis of lethal midline granuloma suspects. Histopathological examination of masses from nasal tissue showed a tumor mass in the form of squamous epithelial proliferation with oval round core, partly pleomorphic, coarse chromatin, eosinophilic cytopasma, prominent core child. In some focus it appears keratinous mass formation. Discussion and result. Based on the results of histopathology examination shows an appropriate picture with the description of keratinizing squamous cell carcinoma. This malignancy is managed surgically. The prognosis depends on the location and size of the tumor